Balancing give and take between patients and their spousal caregivers in hematopoietic stem cell transplantation. Issue 12 (2nd February 2017) - Beattie, Sara; Lebel, Sophie; Petricone‐Westwood, Danielle; Wilson, Keith G.; Harris, Cheryl; Devins, Gerald; Huebsch, Lothar; Tay, Jason
Abstract: Objective: Hematopoietic stem cell transplantation (HSCT) is a demanding treatment. Spouses of HSCT patients assume caregiving responsibilities that can induce feelings of burden and disrupt relationship equity. On the basis of equity theory, we propose a conceptual framework examining the individual and dyadic experience of HSCT patients and their caregivers. The model includes feelings of inequity, patient self‐perceived burden, caregiver burden, and distress. Methods: The HSCT patients and their spousal caregivers were recruited prior to HSCT between March 2011 and September 2012. Each member of the dyad self‐administered a questionnaire package. Results: Seventy‐two dyads were included in the path analyses. Our model demonstrated an inadequate statistical fit; however, with one modification, an adequate to good fit was obtained: χ 2 ( df ) = 6.01(5), normed χ 2  = 1.20, standardized root mean square residual = 0.048, comparative fit index = 0.99, Tucker‐Lewis index = 0.96, and root‐mean‐square error of approximation = 0.05 (90% CI, 0.00‐0.18). As hypothesized, pre‐HSCT caregiver burden mediates the relationship between caregiver underbenefit and caregiver distress. However, patient self‐perceived burden was not associated with patient distress; rather, patient perception of overbenefit was related to patient distress. In our modified model, the results demonstrate that patient overbenefit influenced caregiver burden; however, there was not a reciprocal influence, because caregiver variables did not affect patient variables. Conclusions: Our proposed theoretical framework describes patients' and caregivers' individual experience of distress before HSCT but does not as clearly encompass the dyadic experience. Addressing perceived imbalances and providing psycho‐education on role changes within HSCT dyads before transplantation may be a useful prehabilitation strategy for preventing distress.